Investing in Health 2019 - The National Budget (UNICEF, 2019)
Strengthening the national health system including governance; disease prevention, mitigation and control; health education and promotion, curative services; rehabilitation services; palliative services; control of HIV/ AIDS, Malaria, Tuberculosis & Hepatitis, Human resource (attraction, motivation, retention, training and development); health education, promotion and control; contributing to early childhood development; curative services and health infrastructure development. Over the medium term, the health sector sets out to reduce morbidity and mortality from the major causes of ill health and premature death and reduce disparities therein. Accordingly capital investments will be directed towards development of systems that will use existing facilities, reduce referrals abroad, improving maternal and reproductive health indicators as well as provision of requisite medical equipment.